The impact of grandchild caregiving on depression among grandparents: a scoping review - Hu, Jiajing; Zhang, Nan; Kitcharoen, Patreeya (Frontiers in Public Health, 2025)
IntroductionGrandparents' involvement in grandchild caregiving has become an increasingly common social phenomenon worldwide. Compared with non-caregivers, grandparents' depression may be influenced by caregiving responsibilities. However, existing studies have reported inconsistent findings regarding this association.MethodsFollowing the PRISMA-ScR guidelines, this scoping review systematically mapped the existing literature on the relationship between grandchild caregiving and grandparents' depression. Eight academic databases were searched, yielding 3,174 records. After four screening stages, 30 eligible studies were included for data extraction, analysis, and synthesis.ResultsThe evidence revealed that the effects of grandchild caregiving on grandparents' depression are complex and context-dependent. Differences in caregiving definitions and measurements, grandparent and grandchild characteristics, family structures, and national or cultural contexts contributed to inconsistent results. Six major research gaps were identified: (1) geographical and methodological biases; (2) limited diversity in caregiving measurement; (3) lack of lineage-based analysis (maternal vs. paternal grandparents); (4) insufficient attention to grandchild characteristics; (5) reliance on single depression measures; and (6) inadequate exploration of mediating and moderating mechanisms.DiscussionFuture research should expand geographic coverage, especially in developing regions, and adopt qualitative or mixed-method approaches. It should also diversify caregiving measurements, include lineage-based comparisons, integrate grandchild characteristics, use multidimensional depression tools, and apply theoretical models to explore how caregiving influences mental health. This review is limited by language (English-only publications), exclusion of gray literature, and heterogeneity among included studies, which may reduce comparability.